Integrating Supply Chain Management into Food Estate Models for Enhanced Food Security - Bidarti, Agustina; Irwanto, Dedi (Universitas Panji Sakti, 2025)
This study analyzes the integration of supply chain management (SCM) within a food estate model on lowland swamp agroecosystems to strengthen national food security. A descriptive–analytical survey was conducted for eight months involving 60 farmers from three farmer groups in Muara Belida, South Sumatra. Performance was assessed using the SCOR v13.0 framework, value-added analysis (Hayami method), KPI weighting (ANP), and performance measurement (OMAX with Traffic Light System). Results show an overall SCM performance index of 7.892 (yellow category), with “Deliver” (8.280), “Make” (8.258), and “Return” (8.025) performing relatively well, while “Plan” (7.520) and “Source” (7.758) remain moderate. Policy and managerial implications highlight the need for farmer training, adoption of climate-resilient crop varieties, demand forecasting systems, and formal contractual partnerships to stabilize supply and reduce transaction costs. Findings further reveal that SCM integration enhances value addition at the farmer level and mitigates systemic risks, thereby contributing to food security by reducing logistics costs and building supply chain resilience. This research provides empirical evidence that incorporating SCM into food estate development constitutes a critical strategy for sustainable agro-industrial cluster management in lowland swamps and for achieving national food security.